PEREMPUAN MADURA ANTARA TRADISI DAN INDUSTRIALISASI - Tatik Hidayati, Tatik Hidayati (Institut Agama Islam Negeri Madura)
Abstrac Industry requires competition and competencies. The former is kind of race or contest to allow people to gain the objective, however the latter is an individual skill or capability to gain the objective. Competition goes around social room, therefore competence is a part of individual resource. The social and individual chambers are free from gender, both man and woman have an equal opportunity to reach the individual expected wish. Only those who are able to win the social sphere fight that could be a part of indutrialization, nevertheless those who are not will be left behind. Thus, Madurese woman challenges the fight agains traditional bond which close to social and religious norm and industrial bond which relies on rationality. Based on the fact, industry becomes a social room for Madurese woman. Indeed, this article would view the reality that cannot be avoided by woman—the reality of how the tradition, as social sphere gives meaning on the woman role and how the women fight becomes an important part of them. Kata-kata kunci dialectical, tradition, culture dan industry